2018
DOI: 10.1186/s12933-017-0657-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of apocynin on cardiac remodeling in rats with streptozotocin-induced diabetes mellitus

Abstract: BackgroundIncreased reactive oxygen species (ROS) generation in diabetes mellitus (DM) is an important mechanism leading to diabetic cardiomyopathy. Apocynin, a drug isolated from the herb Picrorhiza kurroa, is considered an antioxidant agent by inhibiting NADPH oxidase activity and improving ROS scavenging. This study analyzed the influence of apocynin on cardiac remodeling in diabetic rats.MethodsSix-month-old male Wistar rats were assigned into 4 groups: control (CTL, n = 15), control + apocynin (CTL + APO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 68 publications
(80 reference statements)
4
39
0
2
Order By: Relevance
“…Research studies have shown that PTDM increase the risk of cardiovascular events including acute myocardial infarction [25]. DM damages the cardiac contractile and relaxation function and is associated with acute myocardial infarction due to hypertrophied [26,27]. It has been reported that DM induces skeletal muscle atrophy [15][16][17], and our research found that Tac-induced PTDM can induce skeletal muscle atrophy.…”
Section: Discussionsupporting
confidence: 60%
“…Research studies have shown that PTDM increase the risk of cardiovascular events including acute myocardial infarction [25]. DM damages the cardiac contractile and relaxation function and is associated with acute myocardial infarction due to hypertrophied [26,27]. It has been reported that DM induces skeletal muscle atrophy [15][16][17], and our research found that Tac-induced PTDM can induce skeletal muscle atrophy.…”
Section: Discussionsupporting
confidence: 60%
“…), dissolved in physiological saline (0.9 % NaCl, 1 D r a f t ml/kg b.w.). Citrate buffer is used for dissolving STZ more frequently than physiological saline (Gimenes et al 2018;Gimenes et al 2015). In order to avoid the effects of citrate buffer on the tested parameters, we used a physiological saline to dissolve STZ, but because of that we applied a higher dose of STZ.…”
Section: Experimental Protocol and Dm Inductionmentioning
confidence: 99%
“…In order to avoid the effects of citrate buffer on the tested parameters, we used a physiological saline to dissolve STZ, but because of that we applied a higher dose of STZ. After 72h fasting blood glucose level was measured, and a glucose level higher than 12.2 mmol/l was considered as a positive for DM (Gimenes et al 2018). In order to confirm the development of diabetes another control group (C0, n = 8) that received physiological solution in one dose and the DM group were used.…”
Section: Experimental Protocol and Dm Inductionmentioning
confidence: 99%
“…Cardiac structures and LV function were evaluated by transthoracic echocardiogram and tissue Doppler imaging using a commercially available echocardiograph (General Electric Medical Systems, Vivid S6 model, Tirat Carmel, Israel) equipped with a 5-11.5 MHz multifrequency transducer. [30][31][32][33] The rats were anaesthetized with a mixture of ketamine hydrochloride (50 mg/kg) and xylazine hydrochloride (1 mg/kg) intramuscularly. A two-dimensional parasternal short-axis view of the left ventricle was obtained at the level of the papillary muscles.…”
Section: Echocardiographymentioning
confidence: 99%